2022
DOI: 10.1021/acssynbio.1c00459
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Biosensor-Based Assay for Quantitative Autoinducer-2 Analysis

Abstract: Bacteria produce and react to interspecies signaling molecules in order to control the expression of genes that are particularly beneficial when they are expressed by a bacterial community. In addition to intraspecies communication, the signaling molecule autoinducer-2 (AI-2) can also serve for interspecies communication between Gram-positive and Gram-negative bacteria and is therefore of particular interest. The analysis and quantification of AI-2 are essential for understanding population density-dependent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…When bacteria reach a critical concentration, they release signal molecules called AIs [ 37 ]. QS is often employed to regulate beneficial genes expressed by a bacterial community, including genes implicated in virulence, biofilm formation, swarming and swimming motilities, stress resistance, and antibiotic resistance [ 39 , 40 ]. Therefore, inhibition of QS communication among bacteria could be used as an alternative strategy to fight multi-drug-resistant bacteria, while any compound that is able to inhibit AI activity without interfering with the growth rate of bacteria can be considered to be a potential QS inhibitor [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When bacteria reach a critical concentration, they release signal molecules called AIs [ 37 ]. QS is often employed to regulate beneficial genes expressed by a bacterial community, including genes implicated in virulence, biofilm formation, swarming and swimming motilities, stress resistance, and antibiotic resistance [ 39 , 40 ]. Therefore, inhibition of QS communication among bacteria could be used as an alternative strategy to fight multi-drug-resistant bacteria, while any compound that is able to inhibit AI activity without interfering with the growth rate of bacteria can be considered to be a potential QS inhibitor [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, it has been demonstrated that both Gand G + bacteria use QS to coordinate gene expression in a cell density-dependent manner [37]. When bacteria reach a critical concentration they release signal molecules which are called AIs [36].QS is often employed to regulate genes that are particularly useful when expressed by a bacterial community, including genes that are implicated in virulence, biofilm formation, swarming and swimming motility, stress resistance, and resistance to antibiotics [38,39]. Therefore, inhibition of QS communication between bacteria could be used as an alternative strategy to fight multidrug resistance bacteria while any compound able to inhibit AI activity without growth inhibition can be considered to be a promising QS inhibitor [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, B has recently been declared an essential element involved in the synthesis of the autoinducer-2 (AI-2) quorum sensing (QS) system. At the same time, active AI-2B is generated by the addition of borate to the AI-2 precursor, being able to amplify the activity of AI-2 and support the secretion of extracellular polymeric substances [122,123].…”
Section: Boron: Essential Element In Host-microbiota Symbiosismentioning
confidence: 99%